Argumentação e raciocínio moral em questões sociocientíficas na formação de professores de ciências : o exemplo da eutanásia - Almeida, Mayara Tavares de (2018)
The aim of this research was to identify the extension of argumentative skills and to establish the possible presence of levels of moral reasoning in the arguments produced by professors of training sciences regarding the socio-scientific issues question (SSI) Euthanasia. One of the ways of working argumentation and moral issues in science teaching is through socio-scientific questions. Socio-scientific issues are characterized by controversial topics that generate discussions that involve values, moral reasoning, and decision-making. In order to carry out this work proposal, I used the focal group as a method of data collection. The focus group was adequate for this research, since I tried to analyze the lines that emerged during the discussion among the participants. These groups were carried out in an extension course offered to chemistry, physics and biology graduates from the Campus Professor Alberto Carvalho at the Federal University of Sergipe. The data records were made through video and audio recordings and were then transcribed for analysis. To analyze the data, I first used Toulmin's argumentative methodological approach to construct the argumentative layouts of each research participant. In a second moment, each of these layouts was analyzed according to Kohlberg's taxonomy of moral reasoning. As a result, I have ascertained that, in general, teachers of training sciences are able to construct arguments, and that levels of moral reasoning show that few people rely on laws to form their moral reasoning in the decision-making process regarding of euthanasia. Regarding the socio-scientific issues approach, I have found that they have considerable potential for development around decision-making and increasing student criticality on issues that permeate the social scene.